Superior nonlinear passive damping characteristics of the bio-inspired limb-like or X-shaped structure. (15th June 2019) - Bian, Jing; Jing, Xingjian
Highlights: The nonlinear damping of the limb-like (LLS) or X-shaped structure is studied. The damping is a nonlinear function of vibration displacement and varies at different frequencies. The damping is high at resonance (large-displacement) but low at other frequencies. The structural parameters can be tuned to achieve a desired passive and nonlinear damping. The study demonstrates an innovative and passive solution for desired nonlinear damping design in engineering. Abstract: Natural biological systems can always demonstrate amazing properties or performance subject to external excitation. The nonlinear damping characteristics of a passive bio-inspired limb-like structure (LLS) or X-shaped structure is studied in this paper with theoretical modelling and experimental validation. It is revealed that, (1) the linear horizontally-placed damper and joint friction can both produce equivalent nonlinear damping in the vertical direction; (2) the equivalent damping characteristic is shown to be a nonlinear function of the vibration displacement and varies at different frequency; (3) the equivalent damping can be beneficially varying with vibration displacement and frequencies, i.e., automatically high at around resonance frequency (for large-displacement vibration) but low at other frequencies (for low-displacement vibration), showing an ideal passive and nonlinear damping property; (4) the structural rod length, asymmetric rod length ratio, layer number, and assembly angle can all affect the equivalent nonlinear damping and thus can be used to tune the damping characteristic to the ideal case conveniently in practice. The results of this study demonstrate an innovative and passive solution for designing desired nonlinear damping characteristics in various engineering practices by employing the LLS.